Effect of Perceived Price and Brand Image on Purchase Decision through Customer Satisfaction, a Study on Azarine Buyers in Malang City - Hariyanti, Novita Tri; Rudijanto W.W, Ery Tri Djatmika; Siswanto, Ely (PT. Riset Press International, 2023)
This study aims to analyze the effect of perceived price and brand image on purchase decision through customer satisfaction with the subject of Azarine skincare buyers in Malang city as respondents. This type of research is quantitative using Path analysis research method using structural equation modeling method with SmartPLS 4.0. Data sample of 270 questionnaires was obtained. Based on the results of the study, it can be concluded that perceived price has a significant positive effect on purchase decision; brand image has no effect on purchase decision; customer satisfaction has a significant positive effect on purchase decision; perceived price has a significant positive effect on customer satisfaction; brand image has a significant positive effect on customer satisfaction; perceived price has an indirect effect on purchase decision through customer satisfaction; brand image has an indirect effect on purchase decision through customer satisfaction. Based on the results of the analysis, the researcher makes suggestions for the azarine skincare brand to expand marketing to various platforms other than Instagram. This will also increase customer satisfaction with the azarine brand itself